Analysis of Factors Affecting the Capital Structure - Parulian, Parulian; Putri, Priska Miranti (DPPM Universitas Pelita Bangsa, 2023)
During the reign of President Joko Widodo, Infrastructure development was the main focus of the government to build a better Indonesian economy. However, most of the budget obtained by infrastructure companies still does not reach the planned target, so other additional funds are needed. The use of funding sources for infrastructure development can certainly affect the capital structure. This can be seen from the average capital structure of infrastructure companies listed on the Kompas 100 Index over the past 8 years, which has decreased. This research was conducted to determine the factors that influence the capital structure which includes: liquidity, profitability, asset structure and company size. The sampling method used is purposive sampling. The samples used in this research are 7 infrastructure companies listed on the Kompas 100 Index in 2015-2022. This research is quantitative with analysis using panel data regression. The results show that asset structure has a significant effect on capital structure, while liquidity, profitability and firm size have an insignificant effect on capital structure.